Análise do desenvolvimento econômico e social do Espírito Santo à luz da transição demográfica - Baiense, Érika Martins (2014)
The purpose of this paper is to analyze the capixaba social and economic development according to the demographic transition. To d o so, first it was sought to contextualize the economic and demographic debate according to different schools in the history of economic thought. In addition, it was analyzed the history of the capixaba economic development in the second half of the twentieth century, through the main indicators used, such as PIB and PIB per capita. Finally, it was observed how was the demographic transition in the Espírito Santo, analyzing if called demographic bonus was absorbed by the labor market capixaba.